2015
DOI: 10.2174/1566524015666150114115427
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K/AKT/mTOR Signaling Pathway in Medulloblastoma

Abstract: Medulloblastoma is the most common malignant childhood brain tumor and is associated with a poor outcome. There is an urgent need to develop novel targeted therapeutic approaches for medulloblastoma, which will arise from an enhanced understanding of the disease at the molecular level. Medulloblastoma has been recognized to be a heterogeneous disease, and no recurrent cancer gene mutations have been found, although many of the mutations described so far affect key intracellular signaling pathways, such as soni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 0 publications
7
64
0
Order By: Relevance
“…Notably, we also observed that down-regulation of SNHG16 could lead to the repression of anti-apoptotic Bcl-2 proteins and PI3K/Akt pathway. Therefore, targeting Bcl-2 proteins and/or PI3K/Akt pathway could be a promising strategy to fight against gliomas [17-19]. Our findings indicated that SNHG16 might be a potential therapeutic target in treatment of gliomas.…”
Section: Discussionmentioning
confidence: 86%
“…Notably, we also observed that down-regulation of SNHG16 could lead to the repression of anti-apoptotic Bcl-2 proteins and PI3K/Akt pathway. Therefore, targeting Bcl-2 proteins and/or PI3K/Akt pathway could be a promising strategy to fight against gliomas [17-19]. Our findings indicated that SNHG16 might be a potential therapeutic target in treatment of gliomas.…”
Section: Discussionmentioning
confidence: 86%
“…It may occur in a context suggestive of a Li Fraumeni syndrome ( TP53 mutations) but no recurrent cancer gene mutations have been found [6, 7]. Nevertheless, many of the mutations described so far affect key intracellular signaling pathways such as sonic hedgehog, Wnt/β-catenin and Phosphoinositide-3-Kinase (PI3K/AKT/mTOR) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Components of the PAM pathway are therefore being considered as potential drug targets [ Table 1] to inhibit the often fatal events of metastasis and cell invasion. [16][17][18] …”
Section: Introductionmentioning
confidence: 99%